Saving behavior in emerging country: The role of financial knowledge, parent socialization and peer influence / Juliana Mohd Abdul Kadir and Amirul Azri Jamaluddin - Mohd Abdul Kadir, Juliana; Jamaluddin, Amirul Azri (Universiti Teknologi MARA Cawangan Pahang, 2020)
The household debt in Malaysia was recorded at 83 per cent of gross domestic product in 2018. This contributed to insufficient amount of saving by household who are mostly not prepared for retirement. Meanwhile, youths in emerging countries however are reported as the main group trapped into the financial problem. The tendency of saving among individual is different from one another due to differences in financial knowledge, parent's socialization, peers influence, self-control and financial stress based on Theory of Planned Behavior. A survey was conducted on 126 students in emerging countries to examine the factors which affected their savings behavior. Structured questionnaires were distributed using convenient sampling technique. Results revealed that parent socialization, financial knowledge and peer influence have a significant effect on students' saving behavior. Findings serve to inform policy makers who are formulating strategies to enhance students' financial knowledge and to maximize the role of parents and peers in order to encourage higher saving behavior in emerging countries.